The Impact of Digital Transformation Technology in Enhancing Organizational Creativity - Salman, Noura Dawood Salman; Al-Abbasi , Adel Abdul Wadood (Journal of Economics and Administrative Sciences, 2025)
The research examines the role of digital technologies in organizational creativity in a telecommunications and information technology company, emphasizing innovation and strategic decision-making fostered by these digital tools such as Internet of Things (IoT), big data analytics, artificial intelligence, cloud computing, and cyber systems. The study followed a quantitative research approach, whereby a Likert-scale questionnaire was administered among 100 senior and middle managers. The collected data were analyzed using SPSS software to measure relationships between digital transformation and creativity dimensions. The analysis found that digital transformation shows a positive and significant impact on organizational creativity. It was found that cloud computing has the highest effect on accelerating innovation through enhanced access to data and process optimization. Cyber systems also provided increased security and operational efficiency, while big data analytics and AI were enablers for better decision-making and creative problem-solving. Some barriers for complete implementation included insufficient strategic planning, as well as resistance to change. The research concludes that an organization needs to have a flexible and adaptive digital strategy to maximize creativity and keep its competitive edge. Future studies should focus on exploring long-term implications of the digital transformation on organizational culture and innovation sustainability.